Analisis Faktor Penggunaan Modal dan Teknologi Melaut dalam Mempengaruhi Tingkat Pendapatan Nelayan di Kabupaten Cilacap - Kristian Cahyandi; Andi Hendrawan (SAINTARA, 2022)
This study aims to analyze the level of capital and the use of fishing technology in its effect on increasing the income of fishermen in Cilacap Regency by taking research samples in South Cilacap District with the largest population of fishing communities among 24 sub-districts in Cilacap Regency. The data used are primary data through direct interviews with respondents and secondary data obtained from the BPS office and the Fisheries and Marine Service Office of Cilacap Regency, using Multiple Linear Regression, with a sample of 100 respondents from the membership of HNSI Cilacap Branch. The results obtained from this study are that the capital factor and the use of technology in fishing significantly affect the income of fishing communities in Cilacap Regency. Among capital and technology, the technological factor that has the most influence on increasing the income of fishermen in Cilacap Regency.